Compressive Strength Of Fiber Reinforced Composite After Immersion In Citric Acid Of Energy Drink - Agnes Robia Ambarioni; Alfina Putri Nurrahmania; Chaerun Mutmainnah; Widya Saraswati; Cecilia G.J.Lunardhi (Universitas Airlangga, 2022)
Background: Energy drink consumption has been popular in people age 18-35 years old. A few literature showed that this drink can cause damage to teeth and composite due to its acidity. The use of fiber reinforced composite has been increasing due to its good mechanical properties and aesthetic. Fiber reinforced composite has fiber shaped fillers that can withstand mastication forces. A restoration material has to face the complex oral environment to succeed clinically. Compressive strength test is needed to predict the durability of restoration materials against mastication forces. Purpose: To determine the effect of energy drink citric acid immersion to fiber reinforced composite compressive strength. Methods: 32 cylinder shaped fiber reinforced composite samples with 8mm tall and 4mm diameter were divided into two groups. The first group was immerse in distilled water (K1) as control, and the second group (K2) was immerse in energy drink citric acid. The samples were immersed in an incubator at ±37⁰C for 7 days. After 7 days, samples were washed in water, dried with tissue, and then undergo compressive strength test with Autograph machine at crosshead speed of 10mm/minute. The data were then analyzed using Independent t-test. Results: The mean compressive strength of K1 group was 1469.63 MPa and K2 group 1439.57 MPa. The mean value of K2 group was slightly lower than K1 group, but statistically, there was no significant difference between the 2 groups. Conclusion: Energy drink citric acid immersion has no effect on fiber reinforced composite compressive strength.